Variability in the growth and mineral nutrition of African clovers - Mugwira, L.M.; Haque, I. (Informa UK Limited, 1991)
A study conducted to develop a classification for Ethiopian clovers based on the performance and phosphorus requirement which has potential for selecting accessions from the rest of the ILCA germplasm suitable for different levels of soil The effects of different P levels on the growth and N and P nutrition of 20 accessions from eleven Ethiopian clover (Trifolium) species were investigated in a glasshouse. The treatments were 0, 12.5, 25, 37.5 and 50 mg P/kg.